A polyclonal antibody against extracellular loops 1 of chNHE1 blocks avian leukosis virus subgroup J infection. (June 2018) - Meng, Wei; Zhou, Defang; Li, Chengui; Wang, Guihua; Huang, Libo; Cheng, Ziqiang
Abstract: Avian leukosis virus subgroup J (ALV-J), an oncogenic retrovirus, induces myelocytomas and other various tumors, leading to great economical losses in poultry industry. It is a great challenge to develop effective preventive methods for ALV-J control due to its antigenic variations in the variable regions of envelope. In present study, we generated a mouse polyclonal antibody targeting the first extracellular loop (ECL1) of chicken Na + /H + exchanger isoform 1 (chNHE1), the receptor of ALV-J, to block ALV-J infection in vitro and in vivo. In ALV-J infected DF-1 cells, chNHE1 expression and the intracellular pH (pHi) were up-regulated with "wave" pattern, indicating that the disequilibrium of ALV-J infected cells associated with chNHE1. Next, we validated that ALV-J infection was significantly blocked with time dependent after treating with anti-ECL1 antibody and accordingly the pHi value were recovered, indicating the blockage of ALV-J infection did not affect Na + /H + exchange. Furthermore, in anti-ECL1 antibody treatment chickens that infected by ALV-J, weight gain and immune organs were recovered, and viral loads were significantly decreased, and the tissue injury and inflammation were reduced significantly from 21 to 35 days of age. The study demonstrated that anti-ECL1 antibody effectively blocks ALV-J infection without affecting Na + /H + exchange, and sheds light on a novel strategy for retroviruses control. Highlights: Anti-ECL1 antibody effectively blocks ALV-J infection. Anti-ECL1 antibody does not affect Na + /H + exchange. Anti-ECL1 antibody alleviates tissues injury caused by ALV-J. Anti-ECL1 antibody sheds light on a novel strategy for retroviruses control.